The role of trigger factors in the occurrence of appropriate ICD shocks and their prognostic implications. (3rd October 2022) - Kleemann, T; Lampropoulou, E; Kouraki, K; Strauss, M; Fendt, A; Mohammad, O; Zahn, R
Abstract: Background: The role of triggers in the occurrence of appropriate ICD shocks due to ventricular tachyarrhythmias is not well known. The aim of the study was to assess the prevalence of trigger factors in appropriate ICD shocks and to analyze their prognostic impact on clinical outcome. Methods: A total of 710 consecutive patients of a prospective single-centre ICD-registry who received a first appropriate ICD shock between 2000 and 9/2021 were analyzed. Results: In 35% of ICD patients with first ICD shock, at least one of the following triggers was found: Ischemia (22%), Compliance (9%), Decompensation (38%), Stress (12%), Technical (5%), Electrolyte/endocrinological disorder (22%) and Medication intoxication (4%) (Table 1). The trigger factors can be summarized under the acronym ICD-STEMi. Patients with trigger associated ICD shocks had a more depressed ejection fraction and presented more often with ventricular fibrillation or electrical storm. The therapy after VT/VF shock in the trigger group comprised trigger optimization in 100% and heart failure optimization in 21% as compared to 0% respectively 10% in the no-trigger group (p<0.001). The ventricular arrhythmia therapy (antiarrhythmics or VT ablation) was not different between both groups (35% in each group). Patients with triggered first ICD shock had an increased 5-year mortality rate (50% versus 38%, p<0.001) (Figure 1). Conclusions: In one third of ICD patients with first appropriate ICD shock, at least one trigger can be identified. Finding a trigger strongly influenced therapy after VT/VF shock. Patients with triggered ICD shock have a higher 5-year mortality rate. The evaluation of trigger factors after the occurrence of ICD shocks is mandatory and can be systematically evaluated using the acronym ICD-STEMi. Funding Acknowledgement: Type of funding sources: None.